BECN1 is a new driver of ferroptosis - Kang, Rui (Autophagy, 2018)
Ferroptosis is a form of regulated cell death caused by iron accumulation and oxidative injury. BECN1 is a key regulator of macroautophagy/autophagy, a catabolic process of degradation induced by starvation or other stressors. Our recent findings reveal a novel alternative mechanism by which BECN1 can promote ferroptosis through the regulation of activity of the cysteine and glutamate antiporter system x(c)(−) in cancer cells. BECN1-dependent autophagy requires the formation of the BECN1-containing class III phosphatidylinositol 3-kinase (PtdIns3K) complex, whereas BECN1-dependent ferroptosis requires the formation of a BECN1-SLC7A11 complex. Furthermore, AMP-activated protein kinase (AMPK) is required for BECN1 phosphorylation to trigger formation of the BECN1-SLC7A11 complex in the process of inhibiting system x(c)(−) activity and inducing lipid peroxidation. These findings suggest that the autophagy-dependent and -independent functions of BECN1 play distinct roles in regulated cell death.